Pengaruh Pelatihan Kerja Terhadap Produktivitas Kerja Pada Karyawan PT. PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Medan - Darmanto Sugondo Sianturi; Risydah Fadilah (Jouska: Jurnal Ilmiah Psikologi, 2022)
This study aims to determine empirically the effect of job training on work productivity of employees of PT. PLN (Persero) implementing unit for customer service (UP3) Medan. The research used is quantitative experimental method One Group Pretest-Posttest Design. The subjects in this study were all employees of PT. PLN (Persero) Customer Service Implementation Unit (UP3) Medan, as many as 60 employees. The results showed that between the average pretest and posttest work productivity of employees, the average pretest data was 164.42 and the posttest average was 271.47, there was a difference of 91.47, where the average posttest score was higher than the posttest score. pretest. The results of the One-Sample Kolmogorov-Smirnov Test analysis showed a significant value of 0.000 0.05. In accordance with the criteria if the significant value 0.05 means that Ho is rejected and Ha is accepted. Thus it can be concluded that by participating in job training can have an influence on the results of work productivity on employees of PT. PLN (Persero) Customer Service Implementation Unit (UP3) Medan. Based on the results of the research that has been done, it can be concluded that the work productivity of employees who take job training is better than the results of work productivity of employees who do not take job training.